How Teachers Interpret And Implement Independent Curriculum: Lesson Learnt From The Field - Ayu Anggraeni; Henny Soepriyanti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The aim of the study was to describe the English Teachers interpretation, implementation, and the challenges in implementing independent curriculum. The research used a descriptive design with a qualitative approach. The data was collected using interviews, observation, and document study. The subjects of this study were 3 English teachers in the seventh grade of junior high school in Lombok Island. The results showed that the English teachers participating in the study had right interpretation of the objectives of English learning in the independent curriculum. They were familiar with the content of English materials, the method of implementing differentiated learning, and method of conducting learning evaluation using formative and summative assessments. However, these English teachers did not have proper interpretation of the content of learning the six skills, including the implementation of text-based approach and student centered learning. Results of the study show that these teachers did not implement independent curriculum optimally because they lacked knowledge in interpreting the components of independent curriculum. The study yields that the challenges faced by English teachers in implementing independent curriculum included (1) the lack of time to prepare the material and (2) the lack of time to internalize the concept of independent curriculum. Ultimately, participants of the study found some difficulties to implement the learning methods in differentiated learning because they lacked time allocation for addressing and adjusting to the demand of new English teaching-learning model.